Electric-field-induced simultaneous diffusion of Mg and H in Mg-doped GaN prepared using ultra-high-pressure annealing. (15th October 2019) - Narita, Tetsuo; Sakurai, Hideki; Bockowski, Michal; Kataoka, Keita; Suda, Jun; Kachi, Tetsu
Abstract: To investigate Mg diffusion during ultra-high-pressure annealing, which activates Mg acceptors in GaN, GaN samples with p–n junctions prepared via epitaxial growth were annealed at 1573 K under 1 GPa. The profiles of Mg diffusion toward the underlying n-type layer cannot be explained by a simple diffusion model. We found that H atoms diffused along with Mg atoms. By considering the suppressed diffusion of positively charged interstitial H atoms due to the electric field in the depletion layer, we could better reproduce the Mg–H diffusion profiles, suggesting that H atoms play a key role in the Mg diffusion process.